Pembentukan Karakter Pancasila untuk Penguatan Civic Disposition di Era Globalisasi - Kurnia, Heni; Lathifah Sandra Devi (Jurnal Mahasiswa Karakter Bangsa, 2025)
This study aims to describe the role of Civics Education (PPKn) teachers in shaping Pancasila character to strengthen students’ civic disposition at SMK Darussalam Ciputat in the era of globalization. The background of this research is based on the importance of character education grounded in Pancasila values in responding to the challenges of global culture, digital technology, and the moral crisis among the younger generation. This study uses a qualitative approach with data collection techniques including observation, documentation, and in-depth interviews with the principal, vice principal of curriculum, Civics Education teachers, and students. According to the findings, teachers of civics education serve as innovators in addressing the problems posed by globalization, facilitators of character education, and role models for Pancasila principles. In addition to incorporating Pancasila values into the design and execution of lessons, educators often use digital media, participatory methods, and model conduct to help students develop good attitudes. Both extracurricular and intramural activities effectively promote values like discipline, social awareness, tolerance, and responsibility. Contextual, collaborative, and project-based learning methodologies are used to address issues such the diversity of social backgrounds, the domination of foreign cultures, and a lack of awareness of digital ethics.